The Paradox of Hospitality: Tourism Development, Cultural and Environmental Sustainability - Winarko, Hilarius Bambang; Putri, Ni Made Mila Octania (Bali Tourism Board, 2025)
Introduction: Bali, renowned for its cultural heritage and natural beauty, faces significant challenges due to rapid tourism-driven property development. This study examines the paradox of hospitality, where economic growth conflicts with cultural and environmental preservation, employing theories of mediated environmental communication and cultural commodification. Problems: Key issues include land conversion threatening food security, gentrification displacing local communities, and foreign land ownership via mixed marriages. Policy gaps, such as inconsistent enforcement of tourist levies and opaque fund management, exacerbate socio-economic disparities and cultural erosion. Discussion: Findings reveal tensions between tourism's economic benefits (job creation, revenue) and its disruptive effects (cultural dilution, environmental degradation). Stakeholders highlight the need for transparent levy allocation, inclusive urban planning, and community-based tourism models to mitigate commodification and marginalization. Conclusion: A holistic approach integrating environmental communication, cultural preservation, and equitable policy enforcement is critical. Recommendations include stricter land ownership laws, participatory decision-making, and leveraging digital media to engage younger generations in sustainable tourism discourse.